Majalah Aktuil dalam Konteks Budaya Musik Rock di Bandung Tahun 1967-1978 - Ageng Rachmad (Fakultas Keguruan dan Ilmu Pendidikan, 2026)
This study will focus on addressing three main research questions: First, what is the history of rock music in Bandung from 1967 to 1978? Second, how did the magazine Aktuil evolve in its presentation of rock music culture in Bandung during the 1967-1978 period? Third, how did the New Order government’s social and media regulations influence Aktuil’s role in promoting rock music culture? These research questions were chosen because no similar studies have yet addressed the topic of rock music in Bandung during the 1967-1978 period, thereby marking a novelty and enriching the writing of local cultural history. The primary research sources are drawn from the archives of a renowned music magazine of that era, namely Aktuil magazine, spanning from issue 01 in 1967 to issue 254 in 1978. The method employed is the historical writing method proposed by Kuntowijoyo, which involves topic selection, heuristics, criticism, interpretation, and historiography. This study is further supported by interviews with three primary informants: first, Mr. Hengki Herwanto, a former journalist at Aktuil magazine from 1973 to 1978; second, Mr. Kin Sanubary, a collector and expert on vintage media from Subang, West Java; and third, Mr. Boy Worang, a cultural figure from Bandung who was also the “golden child” of Remy Sylado, a journalist for Aktuil magazine and Boy Worang’s theater teacher in the 1970s and thus was intimately familiar with the world of the Aktuil magazine press.
FINALISASI oleh Arif 2026 Mei 21
Keywords: Aktuil; Bandung; Magazine; Rock Music